Recent advances in the genomics and therapy of BCR/ABL1-positive and -negative chronic myeloproliferative neoplasms - Mughal, Tariq I.; Hehlmann, Rüdiger; Saußele, Susanne (Leukemia research, 2018)
This review is based on the presentations and deliberations at the 7th John Goldman Chronic Myeloid Leukemia (CML) and Myeloproliferative Neoplasms (MPN) Colloquium which took place in Estoril, Portugal on the 15th October 2017, and the 11th post-ASH International Workshop on CML and MPN which took place on the 6th-7th December 2016, immediately after the 58th American Society of Hematology Annual Meeting. Rather than present a resume of the proceedings, we have elected to address some of the topical translational research and clinically relevant topics in greater detail. We address recent updates in the genetics and epigenetics of MPN, the mechanisms of transformation by mutant calreticulin, advances in the biology and therapy of systemic mastocytosis, clinical updates on JAK2 inhibitors and other therapeutic approaches for patients with MPNs, cardiovascular toxicity related to tyrosine kinase inhibitors and the concept of treatment-free remission for patients with CML.